Expenditures on cellular card of UPV students. - Jaen, Kart Martin P.
This study investigates the differences on monthly expenditures on cellular cards through a set of socio-demographic economic characteristics such as the correspondents' year level, campus location, monthly family income, monthly allowance, household size, sex, distance to nearest source of cell card, number of persons regularly contacted, presence of landline telephone at home, number of messages sent in a day, duration of calls per month and network provider. Furthermore, this study provides the profile of cell phone users in UPV., The results show that UPV students who have cell phones mostly belong to families with a higher family income and have an average of 6 members per household. Majority of the respondents are using Globe network and each of them receive an average monthly allowance of P3210. In terms of monthly expenditures on cellular cards, Miagao-based students spend more on cell cards compared to their counterparts in Iloilo City. Monthly family income and household size does not affect the respondents' capacity to buy cellular cards. One hundred and twenty (120) students of the University of the Philippines in the Visayas were selected as respondents. Each respondent was given a questionnaire consisting of the different factors that might affect their level of expenditures on cellular cards. Data was analyzed using the Kruskal-Wallis statistic with .05 level of significance. The results showed that there was significant difference on respondents' monthly expenditures on cell cards in relation to their monthly allowance, campus location, distance to source of cards, daily number of text messages sent and calls made.